2022
DOI: 10.1002/btm2.10428
|View full text |Cite
|
Sign up to set email alerts
|

Image‐based real‐timefeedback control of magnetic digital microfluidics by artificialintelligence‐empoweredrapid object detector for automated in vitro diagnostics

Abstract: In vitro diagnostics (IVD) plays a critical role in healthcare and public health management. Magnetic digital microfluidics (MDM) perform IVD assays by manipulating droplets on an open substrate with magnetic particles. Automated IVD based on MDM could reduce the risk of accidental exposure to contagious pathogens among healthcare workers. However, it remains challenging to create a fully automated IVD platform based on the MDM technology because of a lack of effective feedback control system to ensure the suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
(105 reference statements)
0
5
0
Order By: Relevance
“…Artificial intelligence (AI) has great potential in medicine, 35 including assisting to evaluate the efficacy and side effects of potential drugs, 36 predicting end‐product quality and composition from early time point in‐process measurements during therapeutic cell manufacturing, 37 and developing an automated in vitro diagnostics platform for an effective feedback control 38 . Even though the animal specimens used in grating interferometers are disease‐free, the CT results (Figures 4, 5, and Figures S2 and S4) demonstrate the feasibility of using AI to learn absorption projections and use virtual projections to reconstruct.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Artificial intelligence (AI) has great potential in medicine, 35 including assisting to evaluate the efficacy and side effects of potential drugs, 36 predicting end‐product quality and composition from early time point in‐process measurements during therapeutic cell manufacturing, 37 and developing an automated in vitro diagnostics platform for an effective feedback control 38 . Even though the animal specimens used in grating interferometers are disease‐free, the CT results (Figures 4, 5, and Figures S2 and S4) demonstrate the feasibility of using AI to learn absorption projections and use virtual projections to reconstruct.…”
Section: Discussionmentioning
confidence: 99%
“…Artificial intelligence (AI) has great potential in medicine, 35 including assisting to evaluate the efficacy and side effects of potential drugs, 36 predicting end-product quality and composition from early time point in-process measurements during therapeutic cell manufacturing, 37 and developing an automated in vitro diagnostics platform for an effective feedback control. 38 Even though the animal specimens used in grating interferometers are disease-free, the CT results (Figures 4, 5 In the presence of pathological processes in breast or lung tissues, this approach may provide radiologists with significantly enhanced contrast compared to routine absorption imaging, as is the case with radiology and CT. In addition, other forms of radiation images could be studied using the cross-modality image learning method, such as neutrons or atomic particles.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Tang et al utilized an AI-empowered rapid object detector for real-time feedback control of magnetic digital microfluidics, which achieved automated in vitro diagnostics. 27 Tostado et al developed an AI-assisted single-cell phenomictranscriptomic platform, which showed great potential in elucidating mechanisms and therapeutic targets against immune response. 28 Misra et al introduced novel deep learning-based techniques for segmenting lesions and distinguishing between benign and malignant cases by analyzing B-mode and strain elastography images.…”
Section: Disease Diagnosismentioning
confidence: 99%
“…A significant trend is the combination of medical diagnosis techniques with the power of artificial intelligence (AI), machine learning and deep learning. For example, Tang et al utilized an AI‐empowered rapid object detector for real‐time feedback control of magnetic digital microfluidics, which achieved automated in vitro diagnostics 27 . Tostado et al developed an AI‐assisted single‐cell phenomic‐transcriptomic platform, which showed great potential in elucidating mechanisms and therapeutic targets against immune response 28 .…”
Section: Disease Diagnosismentioning
confidence: 99%
“…26,27 These sensing and control methods not only enhance the droplet manipulation stability but also optimize the motion performance of the droplet. 26 Imaging technologies, which include background subtraction methods, edge detection, object detection, and image segmentation, [28][29][30][31] are applied to droplet motion recognition. They offer a non-contact, real-time solution for signal acquisition, resulting in rapid and accurate detection and tracking of droplets, even transparent ones.…”
Section: Introductionmentioning
confidence: 99%